Replicability in Art Photography: From Pictorialism to NFT Art / Проблема уникальности в художественной фотографии: от пикториализма до NFT-искусства - YURGENEVA ALEXANDRA L. / ЮРГЕНЕВА А.Л. (Наука телевидения)
The article deals with the idea of uniqueness as an obligatory feature of a work of art in relation to artistic photography. The work is of an overview nature, it notes the methods of giving photographs the features of originality, which emerged at different stages during the century-long history of artistic photography. Earlier studies never focused on the fact that photographers were constantly artificially limiting the technical reproducibility of their works. Addressing this issue defines the novelty of this work. Such a limitation was demanded by an approach in which photographic images had been evaluated from the perspective of traditional art, which affected not only determination of their aesthetic value, but also the legal aspect. And yet, at the turn of the 19th and 20th centuries, the presence of machine nature in photography became a stumbling block in the development of legislative norms on the copyright for pictorialists. The entry of photography into the art market environment gave it the obligation to limit the number of copies based on commercial considerations. The relevance of the study lies in the issues of replicability in digital art, its acquisition and sale. I attempt to interpret the phenomenon of the blockchain system as a concept influencing new ways of understanding and evaluating digital photography in light of its history. The emergence of the NFT format is considered as a moment of overcoming the attitude towards the replicability of artistic photography as a problem rather than its natural property. A suggestion is made that the emergence of a virtual artistic environment has the potential to harmonize this long-standing conflict, and also raises the question of the need for new legal norms in this area. В статье рассматривается проблема применения к художественной фотографии представления об уникальности как обязательной черте произведения искусства. Работа носит обзорный характер, в ней отмечены методы придания фотографии черт неповторимости, которые возникали на разных этапах в течении столетней истории художественной фотографии. Прежде внимание исследователей не концентрировалось на том, что фотохудожники постоянно шли по пути искусственного ограничения технической воспроизводимости своих произведений. Обращение к этому вопросу определяет новизну данной работы. Этого требовал подход к оценке фотоизображений с позиций традиционного искусства, что отражалось не только на определении их эстетической ценности, но и на правовом аспекте. И все же на рубеже XIX–XX вв. наличие машинной природы в фотографии становилось камнем преткновения при разработке законодательных норм об авторском праве фотографов-пикториалистов. Вхождение фотографии в среду арт-рынка наделяло ее обязательствами по ограничению числа копий, исходя из коммерческих соображений. Актуальность исследования заключается в выходе на тему тиражируемости в сфере цифрового искусства, его приобретения и продажи. Совершена попытка интерпретации феномена системы блокчейна как концепции, влияющей на новые пути понимания и оценки цифровой фотографии в свете ее предшествующей истории. Появление NFT-формата рассматривается как момент преодоления отношения к воспроизводимости художественной фотографии как к проблеме, а не как к ее естественному свойству. Высказывается предположение о том, что возникновение виртуальной художественной среды способно гармонизировать этот давний конфликт, а также ставит вопрос о потребности выработки новых правовых норм в этой области.